The predicting the development of anemia of inflammation in young children with acute inflammatory bacterial diseases of the respiratory organs - Pogribna, A. O.; Погрібна, Анастасія Олександрівна (My University, 2022)
The aim of the study. Analysis of pathogenetic relationships in the mechanism of the development of anemia of inflammation in young children with acute inflammatory bacterial diseases of the respiratory organs, and creation of a prognostic mathematical model regarding the probability of its development.
Keywords: тези доповідей